Ultra-thin grating coupler for guided exciton-polaritons in WS2 multilayers - Cho HyunHee; Shin Dong-Jin; Sung Junghyun; Gong Su-Hyun (Nanophotonics)
An ultra-thin transition metal dichalcogenide (TMDC) layer can support guided exciton-polariton modes due to the strong coupling between excitons and photons. Herein, we report the guided mode resonance in an ultra-thin TMDC grating structure. Owing to the strong exciton resonances in TMDCs, a TMDC grating structure shows guided-mode resonance even at a thickness limit of ∼10 nm and is capable of realizing polaritonic dispersion in a monolithic grating structure. We investigated the polarization and thickness dependence of the optical dispersion relations of the tungsten disulfide (WS2) grating structure. In addition, we confirmed that the monolithic WS2 grating coupler can be used to couple the near-field guided exciton-polariton out into the far field. We believe that ultra-thin TMDC layers can facilitate sub-wavelength nanophotonic applications.